Reliability of EMG activity versus bite-force from human masticatory muscles - Gonzalez, Y. (2011)
The reproducibility of electromyographic (EMG) activity in relation to static bite-force from masticatory muscles for a given biting situation is largely unknown. Our aim was to evaluate the reliability of EMG activity in relation to static bite-force in humans. Eighty-four subjects produced 5 unilateral static bites of different forces at different biting positions on molars and incisors, at two separate sessions, while surface EMG activities were recorded from temporalis, masseter, and suprahyoid muscles bilaterally. Intraclass Correlation Coefficients (ICCs) were used, where an ICC of ≥ 0.60 indicated good reliability of these slopes. ICCs for jaw closing muscles during molar biting were: temporalis ipsilateral 0.58 to 0.93 and contralateral 0.88 to 0.91, masseter ipsilateral 0.75 to 0.86 and contralateral 0.69 to 0.88; while during incisor biting were: temporalis ipsilateral 0.56 to 0.81 and contralateral 0.34 to 0.86, masseter ipsilateral 0.65 to 0.78 and contralateral 0.59 to 0.80. For the suprahyoid muscles the confidence intervals were mostly wide and most included zero. Slopes of the EMG activity versus bite-force for a given biting situation were reliable for temporalis and masseter muscles. These results support the use of these outcome measurements for the estimation and validation of mechanical models of the masticatory system.